치과위생사의 치과 유니트 수관관리에 대한 인식과 실천도 - 이성숙; Seong-sook Lee; 김동애; Dong-ae Kim; 송선영; Sun-young Song; 김미연; Mi-yeon Kim; 심하나; Ha-na Shim (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study is to investigate the awareness and practice of dental unit waterline management in dental hygienist. Methods: A self-reported questionnaire was completed by 377 dental hygienists in Seoul and Gyeonggido from March 2 to April 30, 2015. The data were collected by direct visit and informed consent was received after explanation of the study. The questionnaire consisted of general characteristics of the subjects, awareness of dental waterline, practice of dental waterline, and implementation of dental waterline disinfection. Data were analyzed using SPSS 12.0 program. Results: There was a significant correlation between the dental unit waterline disinfection and the appropriateness of the water used for dental treatment(p<0.01, p<0.001). The handpiece was the most commonly used device before treatment and the majority of the subjects answered that they didn``t take water out of ultrasonic scaler and air-water syringe on a daily basis. Conclusions: The majority of the dental hygienists did not know the right understanding and proper practice of dental unit waterline management. To reduce the dental device contamination, the continuing education of waterline management should be done for the dental hygienists.